2022
DOI: 10.1111/faf.12665
|View full text |Cite
|
Sign up to set email alerts
|

Collapse and recovery of seafood wholesale prices in time of COVID‐19

Abstract: The COVID‐19 pandemic has spread around the world, disrupting economies, societies and daily life. Early research anticipated significant negative impacts for the globalized seafood supply network. Here, we explore the impact of the COVID‐19 pandemic on wholesale prices from five major seafood markets around the world. An anomalies analysis was used to establish a 5‐year baseline price for each commodity. Daily price data from 2020 were compared to the baseline to identify collapses (>1.96 SE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…More recently, the COVID-19 pandemic has generated negative effects on the seafood sector and its supply and distribution chain [92,93], such as a reduction in the economic value [94] and demand [95] of seafood, risk to the food systems [96], and impacts on local livelihoods [97]. The aquaculture of A. purpuratus in Chile also experienced these impacts-in line with the finding by Amos et al [98]-and, in 2020, national producers were forced to sell their production at a lower price (Figure 9) in order not to remain with unsold products in stock and generate sufficient income to sustain their production costs. This situation also led to changes in the ownership of national firms in 2022.…”
Section: Economic and Environmental Eventssupporting
confidence: 57%
See 2 more Smart Citations
“…More recently, the COVID-19 pandemic has generated negative effects on the seafood sector and its supply and distribution chain [92,93], such as a reduction in the economic value [94] and demand [95] of seafood, risk to the food systems [96], and impacts on local livelihoods [97]. The aquaculture of A. purpuratus in Chile also experienced these impacts-in line with the finding by Amos et al [98]-and, in 2020, national producers were forced to sell their production at a lower price (Figure 9) in order not to remain with unsold products in stock and generate sufficient income to sustain their production costs. This situation also led to changes in the ownership of national firms in 2022.…”
Section: Economic and Environmental Eventssupporting
confidence: 57%
“…Finally, given the rapid adaptation of small-scale fisheries sectors to abrupt shocks in the marketing system [94], it is necessary to assess small-scale production units that allow them to sell their products to other intermediaries or to the canning industry. For its part, the COVID-19 pandemic has resulted in emerging challenges, such as the scarcity of inputs, the impossibility to sell the product, the lack of transport for the supply of seafood [93], and others such as the low price of seafood, which without being the most important one, has a great impact on the subsistence of producers [93,98].…”
Section: Challenges For Argopecten Purpuratus Industry In Chilementioning
confidence: 99%
See 1 more Smart Citation
“…Fbprophet had been used to predict prices of cryptocurrency and even energy demands (Chaturvedi et Despite our results had been obtained through a univariate analysis, its low error metrics showed that the utilization of LSTM neural networks and Fbprophet algorithm may be applicable to the study of prices variation of seafood items opening the door to more complex analysis evaluating other features. Once other variables weren't evaluated in the modelling, we have no direct evidence about which are the main in uences in the price's uctuation in PSLC sardine, however, peaks of volatility after 2020 may be an indicator of the COVID-19 impact in seafood prices in Brazilian market, once it also impacted important seafood markets worldwide (Akter, 2020;Amos et al, 2022). For further studies, the acquisition and evaluation of more variables are indicated once food prices may be in uenced by factors such as oil prices, which in some market situations in uence food items price volatility (Hau et al, 2020), being helpful to build more robust analysis and contribute to understand the prices dynamics of seafood items.…”
Section: Discussionmentioning
confidence: 98%
“…Impacts of COVID-19 on the wholesale prices of seafood products [27] and agricultural products [28] , [29] have been documented. On the one hand, the price changes downstream in general affect prices upstream in the supply chain.…”
Section: Introductionmentioning
confidence: 99%